Assessment and Comparison of Greenness of UV-Spectroscopy Methods for Simultaneous Determination of Anti-Hypertensive Combination - Yenduri, Suvarna; Varalakshmi, H N; Koppuravuri, Naga Prashant (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Environmentally destructive analytical research practices, such as using and releasing hazardous solvents and reagents into the atmosphere, have brought up serious concerns regarding the ecological impact of these actions. By checking greenness of the methods, ecological challenges can be minimized. This gives a brief idea about its extent of effect on environment to the analyst. Aim This work was designed to select the ecofriendly method for the estimation of amlodipine besylate and telmisartan from the existing UV spectroscopy methods. Materials and Methods In this work the methods available to estimate these two drugs by UV-spectroscopy are collected and assessed in terms of their greenness using a variety of green metrics like National Environmental Method Index, Raynie and Driver tool/AGP, Analytical Eco Scale and AGREE. This considers the Green Analytical Chemistry twelve principles. Results and Conclusion The degrees of greenness for the selected methods were shown as pictograms for some metrics and scores in some other cases using the assessment tools. The greenness of the selected methods was tabulated and compared for the best choice. The study gave a clear idea about the pros and cons of the methods with respect to greenness and made it easy for the analyst to select the best eco-friendly method.
Keywords: Green analytical chemistry; Green Metrics; UV-spectroscopy; Eco-friendly; Green solvents